Perspectives on prolonged nocturnal invasive mechanical ventilation - Robert L Vender (Journal of Mechanical Ventilation)
The utilization of invasive mechanical ventilation (IMV) has become common practice for a large and expanding number of patients with chronic respiratory failure resultant from several medical diseases and disorders. Although protocols and guidelines for the acute management of respiratory failure exist with expansive evidence-based data, the chronic management of similar patients outside the Intensive Care Unit (ICU) setting requiring extended and prolonged durations on invasive mechanical ventilation (IMV) has been much less clearly defined. In addition, the vast majority of such care is administered outside the acute hospital environment. Most adults requiring chronic mechanical ventilatory support include two general populations: 1) patients with severe intrinsic lung disease who have experienced acute respiratory failure initially managed in ICU settings and 2) patients with progressive neuromuscular diseases. When attempts at weaning, ventilator liberation, and achievement of successful full-time continuous spontaneous ventilation fail, mechanical ventilation management often reverts to part-time (predominately nighttime) nocturnal invasive mechanical ventilation (NIMV) with periods of spontaneous breathing duration awake daytime hours. Such a practice pattern has been advocated by peer-reviewed published expert opinions. Yet such a pattern would appear to potentially exclude many patients from eventual total weaning, ventilator liberation and even decannulation and progression to independent sustained life-long spontaneous ventilation. In addition, such a ventilator management program may not even be indicated for patients with progressive neuromuscular disorders in the absence of an acute concomitant lung disease. The predominate physiological factors prohibiting sustained spontaneous ventilation would appear to be 1) inspiratory muscle (predominantly diaphragmatic) fatigue, which per definition should be correctable with appropriate managment including the concept of ventilatory muscle rest (VMR) and/or 2) inspiratory muscle weakness resultant from a pathological disease entity. However, the elusive nature of defining, appropriately monitoring, and subsequent therapy of diaphragmatic fatigue clearly hinders the practical management of this large volume of patents thus rendering them “Ventilator Dependent”. In addition, the absence of disease modifying therapies for chronic progressive neuromuscular disorders contributes to the eventual outcome of fulminant respiratory failure. The purpose of this narrative review is not to challenge but rather to attempt to validate or not validate the concept that nocturnal invasive mechanical ventilation (NIMV) is a “valid” goal of IMV on a chronic long-term basis.